EFFECTS OF PROBLEM-SOLVING INSTRUCTIONAL TECHNIQUE AND COGNITIVE STYLE ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN GENETICS IN ANAMBRA STATE (UNIZIK Journal of STM Education, 2021)
The study investigated the effect of problem-solving technique and cognitive style on students’ academic achievement in genetics in Onitsha Education Zone. Four research questions guided the study while four hypotheses were tested at 0.05 level of significance. Quasi-experimental research design was adopted for the study. The population of the study consists of 5,397 Senior Secondary school students in the 20 co-educational secondary schools in 32 public Secondary Schools in Onitsha Education zone. A sample consisting of 120 (52 Male and 68 Females) SSII biology students from two schools was used for the study. Two instruments tagged Group Embedded Test (GEFT) and Genetics Achievements Test (GAT) were used to collect data for the study. Data were collected with a 40-item genetics achievement test and 20-item group embedded figure test. Kuder-Richardson (KR-20) reliability method was used to determine the reliability of the instrument. Mean was used to answer the research questions. The null hypotheses were tested at 0.05 level of significance using analysis of covariance (ANCOVA). Findings of the study revealed that students’ with field independent and field dependent cognitive style taught genetics using problem-solving technique achieved higher than those taught using the expository method. Problem-solving technique had more effect on students’ achievement in genetics than expository method. Gender was not a significant factor in determining students’ achievement in genetics. Based on the findings of the study, it was recommended among others that teachers should use problem-solving technique as one of the instructional strategies for teaching biology since it has been found to be more effective in enhancing students’ academic achievement in biology (genetics) than the expository methods.
Keywords: Problem-solving; cognitive style; achievement; genetics